2018
DOI: 10.1002/hep4.1247
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Nucleos(t)ide Analogue Therapies for Chronic Hepatitis B Infection: A Systematic Review and Meta‐Analysis

Abstract: Successful treatment outcomes for chronic hepatitis B virus (HBV) infection requires high levels of adherence to treatment. We searched three databases and abstracts from two conferences up to January 2018 for studies reporting the proportion of patients who were adherent to HBV antiviral therapy and pooled data using random effects meta‐analysis. We included 30 studies, providing data for 23,823 patients. Overall, adherence to treatment was 74.6% (95% confidence interval [CI] 67.1%‐82.1%). Adherence was simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 47 publications
2
28
0
Order By: Relevance
“…Our data demonstrated a 29% NA persistence level during year 1 of follow-up, which decreased to 14% during year 2 of follow-up. Although most of the published literature on CHB treatment has evaluated adherence [30][31][32], and indicated trends similar to those observed in our study with suboptimal adherence and a decrease in adherence overtime, Chotiyaputta, et al reported that persistence decreased to 94.2% after 3 months, 77.6% after 6 months, 74.7% after 9 months, and 73.4% after 12 months on medication among patients with CHB with no prior exposure to NAs [33].…”
Section: Discussionsupporting
confidence: 86%
“…Our data demonstrated a 29% NA persistence level during year 1 of follow-up, which decreased to 14% during year 2 of follow-up. Although most of the published literature on CHB treatment has evaluated adherence [30][31][32], and indicated trends similar to those observed in our study with suboptimal adherence and a decrease in adherence overtime, Chotiyaputta, et al reported that persistence decreased to 94.2% after 3 months, 77.6% after 6 months, 74.7% after 9 months, and 73.4% after 12 months on medication among patients with CHB with no prior exposure to NAs [33].…”
Section: Discussionsupporting
confidence: 86%
“…With new global goals to increase numbers of people with CHB on treatment, assessing and maximizing adherence will become an increasing challenge in all settings. A recent systematic review including 30 studies with different adherence measures estimated overall adherence to treatment in CHB with oral therapy was 75% and was similar in both high and low income settings [11]. Factors that have been shown to be related to poor adherence have included forgetting and change to routine, younger age, higher physician turnover and recent initiation of therapy [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review including 30 studies with different adherence measures estimated overall adherence to treatment in CHB with oral therapy was 75% and was similar in both high and low income settings [11]. Factors that have been shown to be related to poor adherence have included forgetting and change to routine, younger age, higher physician turnover and recent initiation of therapy [11][12][13][14][15]. Adverse reactions to medication can also result in poor adherence however antivirals for CHB have a low side effect profile and rarely adverse outcomes [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, different adherence rates for chronic HBV treatment was found in the previous published literature. On the one hand a high adherence rate of 81-99% were reported in the systemic review of Lieveld et al [15], but on the other hand, a lower adherence rate of about 75% was found in the recently published literature, including original studies and systemic review and meta-analysis [16,17]. These differences can be accounted by the varying methods of adherence assessment used in the different studies.…”
Section: Discussionmentioning
confidence: 99%